Biochemical and molecular features of tetrahydrobiopterin deficiency in Fujian Province, southeastern China - Qiu, Xiaolong; Zhao, Peiran; Luo, Jinying; Li, Guilin; Deng, Lin; Zeng, Yinglin; Xu, Liangpu; Zhou, Jinfu (Frontiers in Genetics, 2023)
The estimated prevalence of tetrahydrobiopterin deficiency (BH4D) and the mutational spectrum of the causal 6-pyruvoyl-tetrahydropterin synthase (PTS) gene vary widely according to race and region. This study assessed the prevalence and genetic characteristics of BH4D in Fujian Province, southeastern China. A total of 3,204,067 newborns were screened between 2012 and 2022 based on the phenylalanine level and the phenylalanine/tyrosine ratio in dried blood spots. Differential diagnosis was determined by the urine purine spectrum, dihydropteridine reductase activity in red blood cells, and genetic testing. The PTS mutation spectrum and genotypes were determined by next-generation sequencing. A total of 189 newborns were diagnosed with hyperphenylalaninemia (HPA) over the study period, including 159 with phenylalanine hydroxylase deficiency and 30 with BH4D. Therefore, the prevalence of BH4D in Fujian was 9.36 per 1,000,000 live births (30/3,204,067) and the proportion of BH4D among patients with HPA was 15.87% (30/189). A total of 58 PTS alleles were identified in the 29 patients with PTS deficiency (PTPSD), and those alleles were composed of 10 different variants, including eight missense variants and two splice-site variants. The most prevalent variants were c.155A>G, p.Asn52Ser (44.83%); c.259C>T, p.Pro87Ser (39.66%); and c.84-291A>G, p.Tyr27Argfs*8 (3.45%). The predominant genotype was c [155A>G]; [259C>T] (11/29, 37.93%). The prevalence of BH4D and the spectrum of associated PTS mutations were successfully determined for the first time in Fujian Province, southeastern China. Since the mutation spectrum of PTS is region-specific, such data will facilitate molecular diagnosis and genetic counseling in PTPSD cases.